Financial and Operational Performance of Cooperatives in Northern Province - Mangaleswaran, T.; Alfred, M. (University of Jaffna, 2014)
There is huge investment employed during the last four years by cooperative societies in the Northern Province. Since the overall performance of them are not at the expected level, there is a need to examine them in terms of their financial and operational performance of the cooperatives so as to establish their current status in terms of assets utilization, performance of their business activities and see whether they satisfy the needs of their stakeholders. In this study, the researchers adopted multiple methods such as focus group discussion, key informants interview, and direct observation for primary data collection. The researchers designed tools for collecting data from different stakeholders of the co-operative societies. The secondary data were collected from the documents related to all the activities from 2009/2010 to 2012/2013. Though considerable amounts of resources are available for the cooperatives, it seems that the Board of Directors and the management do not know how to utilize the resources at their maximum and get benefit from them. The examination of their business activities indicates that most of the activities are very relevant and potential to the societies. However, most of the activities are running at losses. This raises questions as to why those activities are running at a loss. After the civil war, the cooperatives concerned received altogether Rs. 231.56 million as support from the organizations such as UN agencies, International NGOs, Local NGOs and the Government. However, it was found that the returns out of these investments are meager and inefficient management is the challenge that has to be addressed immediately to revive them
Keywords: Performance; Performance; Finance